Investigation of heat input effects on the joint characteristics of CMT welded Aa6061 sheets. (May 2023) - Selvamani, ST; Bakkiyaraj, M; Balasubramanian, V; Ramesh, A; Vijayakumar, MD
Cold Metal Transfer (CMT) arc welding is an updated version of the GMAW process, in which heat input is significantly reduced due to the push-pull action of filler wire feeding during welding. The aluminium alloy sheets are welded by the CMT arc welding process using different heat input levels in this research work. The temperature distribution during welding is experimentally measured with the help of an infrared thermometer, and finite element analysis (volumetric heat source model) is used to predict the temperature distribution, and these results are equated. The influence of heat input on joint characteristics such as bead geometry, microhardness variation, microstructure analysis and tensile properties is also being investigated experimentally. The temperature study reveals that the results of numerical modelling for temperature distribution using various heat inputs were very close to the experimental condition, with a less significant difference ±5. In addition, the well-controlled heat input at 210 J/mm was attributed to eradicating porosity, which was confirmed by Non-destructive evaluation, macrostructure and microstructure analysis. As a result, the joint produced a better tensile strength of 241 MPa due to the achievement of fine grain refinement of 17 µm in the weld zone, reduced heat affect zone, and 6.45% volume fraction of Mg2 Si particles. The intercept length of 18.937 microns is measured as the average value, and the misorientation angle of 25.2922 was also found as the average in the fusion zone, which is more significant when compared to the base metal value of 20 μm.